Green Wars : Conservation and Decolonization in the Maya Forest - Ybarra, Megan (Book collections on Project MUSE., 2018)
"Green Wars challenges international conservation efforts, revealing through in-depth case studies how "saving" the Maya Forest facilitates racialized dispossession. Megan Ybarra brings Guatemala's 36-year civil war into the perspective of a longer history of 200 years of settler colonialism to show how conservation works to make Q'eqchi's into immigrants on their own territory. Even as the post-war state calls on them to claim rights as individual citizens, Q'eqchi's seek survival as a people. Her analysis reveals that Q'eqchi's both appeal to the nation-state and engage in relationships of mutual recognition with other Indigenous peoples -- and the land itself -- in their calls for a material decolonization."--Provided by publisher.